The Effect Of Profitability, Company Value, And Financial Distress On Earnings Management: Case Study on Property and Real Estate Sector Companies Listed on the Indonesia Stock Exchange 2018-2022 - Pradipto, Didit; Nabhan, M Fahmi; Suharmiati, Suharmiati (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
The aim of this study is to examine the effect of the independent variables that consist of profitability was proxied by Return on Asset Ratio, firm value was proxied by Price to Book Value, and Financial Distress was proxied by Altman Z”-Score toward dependent variable, Earning Managements, was proxied by Discretionary Accruals of Modified Jones Model. The sample from this research are real estate and property companies that listed in Bursa Efek Indonesia from 2018 – 2022. The companies chosen to be sampled in this research were chosen using purposive sampling method. The data and model testing include classic assumption (normality test, multicolinearity test, and heteroscedasticity test), statisctic descriptive analysis, and hypothetical test (T-test and coeficient determinination test). The classic assumption states the data are able to be used in the research. The T-test show partially profitability has negative effect and does not have significant effect on earning managements, firm value has significant and positive effect on earning managements, and financial distress show positive and does not have significant effect on earning managements. Meanwhile, the coeficient determination test shows that profitability, firm value, and financial distress have 52,7% effect in earning managements. Key words: Profitability, Firm Value, Financial Distress, Earning Managements